Los arrecifes coralinos de Golfo Dulce, Costa Rica: aspectos ecológicos* - Cortés, Jorge (1992)
The coral reefs and coral cornmunities in Golfo Dulce, southem Pacific Coast of Costa Rica, are described. The Inner Gulf reefs are characterized by a high topographic relief, low coral diversily and live coral covegage, and high dead coral coverage. The reefs can be zoned into: l . A reef-flat zone, where dead Pocíllopora and Psammocora are predorninant, togetber witb live and dead rnicroatolls of Porí/es loba/a. 2. A reef-edge zone, where tbere is a marked change in physiognorny, from a relatively horizontal reef-flat to an a1rnost vertical reef-fronL Tbis is tbe zone witb highest live coral coverage and is for tbe most part Porí/es loba/a. 3. A reef-front, extending frorn 2 to 10 m deptb, made up mainly of dead Porí/es lobala. The Outer GuIf reeís are characterized by a low topograpbic relief, high live coral coverage and diversity, and low dead coral coverage. A total of nine sc1eractinian species were found in Golfo Dulce. Most abundant are PorÍJes lobala, Psammocora stella/a and Pocillo poro damicornis, which have also becn present tbere tbroughout tbe Holocene. Twenty four fish species were observed in two reefs. Most of them are important for tbe artesanal fisheries of Golfo Dulce. Otber species are important recf herbivores or corallivores. Intemal ro- ral bioerosion (chief1y boring bivalves: Lithophaga) is more important tban extemal bioerosion. . Enviromnental conditions at Golfo Dulce were conducive to reef growth in the recent past but are now deteriorating as a result of inreased sediment loads. Deforestation, pemicioÍls agricultural practices and miniog in tbe Golfo Dulce watershed must be brought under control and erosion reduced. H tbese were possible a program of reef rehabilitation by transplanting corals could be started to recover sorne of the reefs.